Waiting-List and early posttransplant prognosis among ethnoracial groups: Data from the organ procurement and transplantation network - Wu, Yangyang; Lv, Kaikai; Hao, Xiaowei; Lv, Chao; Lai, Wenhui; Xia, Xinze; Pang, Aibo; Yuan, Qing; Song, Tao (Frontiers in Surgery, 2023)
Ethnoracial differences in waiting-list mortality among candidates listed for kidney transplantation (KT) in the United States remain unclear. We aimed to assess ethnoracial differences in waiting-list prognosis among patients listed for KT in the United States in the current era.We compared waiting-list and early posttransplant in-hospital mortality or primary nonfunction (PNF) among adult (age ≥18 years) white, black, Hispanic, and Asian patients listed for only KT in the United States between July 1, 2004 and March 31, 2020. Of 516,451 participants, 45.6%, 29.8%, 17.5%, and 7.1% were white, black, Hispanic, and Asian, respectively. Mortality on the3-year waiting list (including patients who were removed for deterioration) was 23.2%, 16.6%, 16.2%, and 13.8%, and the cumulative incidence of posttransplant in-hospital death or PNF after KT was 3.3%, 2.5%, 2.4%, and 2.2% in white, black, Hispanic, and Asian patients, respectively. White candidates had the highest mortality risk on the waiting list or of becoming too sick for a transplant, while black (adjusted hazard ratio, [95% confidence interval, CI], 0.67 [0.66–0.68]), Hispanic (0.59 [0.58–0.60]), and Asian (0.54 [0.52–0.55]) candidates had a lower risk. Black KT recipients (odds ratio, [95% CI] 1.29 [1.21–1.38]) had a higher risk of death before discharge or PNF than white patients. After controlling confounders, black recipients (0.99 [0.92–1.07]) had a similar higher risk of posttransplant in-hospital mortality or PNF as white patients than Hispanic and Asian counterparts. In conclusion, race and ethnicity affect the prognosis of candidates listed for KT and the early posttransplant prognosis of KT recipients. Despite having better socioeconomic status and allocated better kidneys, white patients have the worst prognosis during waiting period and in the early posttransplant period. KAS implementation was associated with improved waiting-list survival across all four races but impaired early posttransplant prognosis for white and black recipients.